Kaposi's sarcoma-associated herpesvirus expresses an array of viral microRNAs in latently infected cells - Cai, Xuezhong (National Academy of Sciences, 2005)
MicroRNAs (miRNAs) are an endogenously encoded class of small RNAs that have been proposed to function as key posttranscriptional regulators of gene expression in a range of eukaryotic species, including humans. The small size of miRNA precursors makes them potentially ideal for use by viruses as inhibitors of host cell defense pathways. Here, we demonstrate that the pathogenic human herpesvirus Kaposi's sarcoma-associated herpesvirus (KSHV) encodes an array of 11 distinct miRNAs, all of which are expressed at readily detectable levels in latently KSHV infected cells. Individual KSHV miRNAs were expressed at up to 2,200 copies per cell. The KSHV miRNAs are expressed from what appears to be a single genetic locus that largely coincides with an ≈4-kb noncoding sequence located between the KSHV v-cyclin and K12/Kaposin genes, both of which are also expressed in latently infected cells. Computer analysis of potential mRNA targets for these viral miRNAs identified a number of interesting candidate genes, including several mRNAs previously shown to be down-regulated in KSHV-infected cells. We hypothesize that these viral miRNAs play a critical role in the establishment and/or maintenance of KSHV latent infection in vivo and, hence, in KSHV-induced oncogenesis.